Change and challenge for Pastoralists - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A ten-year study by ILCA of the Borana rangelands of southern Ethiopia has revealed 8 system under pressure, with increasing resource degradation and worsening food security for the people. Profound changes are taking place in what was once a...